Modelling interception loss from evergreen oak Mediterranean savannas: Application of a tree-based modelling approach - Pereira, F. L.; Gash, J. H. C.; David, J. S.; David, T. S.; Monteiro, P. R.; Valente, F. (Agricultural and Forest Meteorology, 2009)
In a previous study, it was shown that an isolated, fully saturated tree-crown behaves like a wet bulb, allowing evaporation of intercepted rainfall to be estimated by a simple diffusion equation for water vapour. This observation was taken as the basis for a new approach in modelling interception loss from savanna-type woodland, whereby the ecosystem evaporation is derived by scaling up the evaporation from individual trees, rather than by considering a homogeneous forest cover. Interception loss from isolated trees was estimated by combining the aforementioned equation for water vapour ﬂux with Gash’s analytical model. A new methodology, which avoids the subjectivity inherent in the Leyton method, was used for estimating the crown storage capacity. Modelling performance was evaluated against data from two Mediterranean savanna-type oak woodlands (montados) in southern Portugal. Interception loss estimates were in good agreement with observations in both sites. The proposed modelling approach is physically based, requires only a limited amount of data and should be suitable for the modelling of interception loss in isolated trees and savannatype ecosystems
Keywords: Gash analytical model; Isolated trees; Quercus ilex; rainfall interception; Savannas; Wet bulb temperature

Rainfall interception by an isolated evergreen oak tree in a Mediterranean savannah - David, T. S.; Gash, J. H. C.; Valente, F.; Pereira, J. S.; Ferreira, M. I.; David, J. S. (Hydrological Processes, 2006)
Redistribution of ground-level rainfall and interception loss by an isolated Quercus ilex tree were measured over 2 years in a Mediterranean oak savannah. Stemﬂow, meteorological variables and sap ﬂow were also monitored. Rainfall at ground level was measured by a set of rain-gauges located in a radial layout centred on the tree trunk and extending beyond the crown limits. Interception loss was computed as the difference between the volume of rainwater that would reach the ground in the absence of the tree and the volume of water that actually fell on the ground sampling area (stemﬂow included). This procedure provided correct interception loss estimates, irrespective of rainfall inclination. Results have shown a clear non-random spatial distribution of ground-level rainfall, with rainwater concentrations upwind beneath the crown and rain-shadows downwind. Interception loss amounted to 22% of gross rainfall, per unit of crown-projected area. Stand interception loss, per unit of ground area, was only 8% of gross rainfall and 28% of tree evapotranspiration. These values reﬂect the low crown cover fraction of the stand (0Ð39) and the speciﬁc features of the Mediterranean rainfall regime (predominantly with few large storms). Nevertheless, it still is an important component of the water balance of these Mediterranean ecosystems
Keywords: interception loss; Isolated trees; Quercus ilex; rainfall interception; rainfall redistribution